MENINGKATKAN MINAT DAN HASI BELAJAR MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN MELALUI MODEL PEMBELAJARAN MEDIA KARTU BILANGAN SISWA KELAS 1 SD NEGERI 18 KAMPUNG PANSUR KECAMATAN KOTO XI TARUSAN - Yurmina Yurmina (STKIP Pesisir Selatan, 2018)
ABSTRACTThis research was conducted on learning Mathematics at SD Negeri 18 Kampung Pansur including (1) low student learning outcomes. (2) Lack of student interest in learning mathematics. (3) The learning method used by the teacher is conventional, the teacher speaks more and students listen. (4) Learning media used is not effective and interesting. This study aims to